Development of the strategic financial engineering accounting system - Proskurina, Nelia; Gryn, Viktoriia (Public Policy and Accounting, 2021)
The necessity of developing information add-ins to the financial accounting system for the formation of additional strategic information is revealed. Additional types of information needed by stakeholders to make strategic decisions are highlighted. Historical aspects of the emergence of strategic accounting engineering are considered. The main ways of developing engineering principles for building a strategic financial accounting system are highlighted and analyzed. The sequence of formation of derivative strategic balance sheets is developed through the development of an engineering system of financial accounting of an enterprise, which includes the following stages: 1) aggregation of elements of financial statements; 2) implementation of corrective operations; 3) implementation of transformational (hedged) operations; 4) implementation of strategic operations; 5) implementation of hypothetical operations. The necessary sources of information for forming a derivative strategic balance sheet of an enterprise are disclosed. A model for generating a derivative strategic balance sheet of an enterprise has been developed, which allows calculating engineering indicators (net assets, net assets after adjustments, hedged net assets, strategic net assets, net liabilities) for analyzing the results of strategic enterprise management.